Efektifitas Model Latihan untuk Meningkatkan Penguasaan Teknik Pukulan Backhand Drive untuk Atlet Bulutangkis - Rezza Adiluhung Prasetya; Anjas Asmara Subekti; Brian Kurniawan Widianto; Koko Prasetyo; Tri Sutrisno (Universitas Mercu Buana Yogyakarta, 2025)
The purpose of this activity is to determine the effectiveness of the training model to improve the mastery of the backhand drive stroke technique for badminton athletes. This activity was carried out at PB PMS Jl Kediri Tengah, Nusukan, Banjarsari, Surakarta. The population and sample used were 10 PMS Surakarta badminton athletes. The Data Analysis Technique used in this study was using the Frequency Distribution Normality Test. The homogeneity test of population variance was calculated using One Way Anova SPSS. In this homogeneity test, the Levene's Test was used. Based on the results of the effectiveness test carried out, the new method had better results than the group using the old method. The number of results obtained from the two groups, namely the treatment group 1866 while the control group 1443, with these results it can be concluded that the training model has a positive effect on improving the backhand drive stroke technique skills for beginner category badminton athletes. Based on this study, it can be concluded that the backhand drive stroke training model for beginner category badminton athletes is considered effective in improving the backhand drive stroke technique skills.